Alternatif Kebijakan Publik dalam Penanganan Konflik Perguruan Silat Persaudaraan Setia Hati Terate dan Perguruan Silat Persaudaraan Setia Hati Winongo Tunas Muda - KHOYRUL ANWAR (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2023)
The conflict between the Setia Hati Terate Brotherhood Martial Art College and the Setia Hati Winongo Tunas Muda Brotherhood Martial Art College in Madiun City has been going on for a long time. Actually the government has made various efforts with security forces and leaders of martial art college, to overcome the frequent conflicts. Basically, the root of the problem has been found, but the policy strategy for conflict resolution has not yet provided a solution that can reconcile the two warring parties. This research aims to provide alternative policies needed to carry out causative treatment in order to heal conflicts between the Setia Hati Terate Brotherhood Martial Art College and the Setia Hati Winongo Tunas Muda Brotherhood Martial Art College. This research is descriptive qualitative with a case study approach (case study). The data obtained from the results of interviews, document searches and literature are described qualitatively. To obtain alternative policies, it is carried out using Franklin and the equivalent alternative method. The results of the study showed that there were 2 (two) causes of violence or conflict between the PSHT and PSHW martial art College that had happened so far, namely the tendency of excessive fanaticism towards their respective martial art college and the desire to dominate territory/power between the martial art schools. An alternative policy that can be formulated by local governments and stakeholders is the Issuance of Regional Regulations concerning Limiting the Activities of Martial Art Colleges and Controlling the Martial Art College Symbol Monument.